2012
DOI: 10.1089/gtmb.2012.0055
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CYP2D6 and CYP2C19 Polymorphisms Associated with Poor Metabolizer Phenotype in Five Amerindian Groups and Western Mestizos from Mexico

Abstract: Background: The distribution of polymorphisms in the CYP2D6 and CYP2C19 genes allows inferring the potential risk for specific adverse drug reactions and lack of therapeutic effects in humans. This variability shows differences among human populations. The aim of this study was to analyze single-nucleotide polymorphisms related to a poor metabolizer (PM) phenotype in nonpreviously studied Amerindian groups and Mestizos (general admixed population) from Mexico. Methods: We detected by SNaPshot Ò different polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
8
20
2
3
Order By: Relevance
“…[29][30][31][32] In both our patient and volunteer MM samples, we observed a predominance of the wild-type CYP2C19*1 allele, a low frequency of CYP2C19*2 and an absence of CYP2C19*3 allele, as it has been previously reported. [33][34][35][36][37][38] The frequency of CYP2C19*17 allele found in the present study (MM from Central Mexico) shows a minor nonsignificant difference from that found in a recent report in MM from the state of Jalisco (0.09 and 0.14, respectively). 38 The frequency of ABCB1 3435C4T in the MM population studied here is similar to that found in previous reports.…”
Section: Discussioncontrasting
confidence: 91%
“…[29][30][31][32] In both our patient and volunteer MM samples, we observed a predominance of the wild-type CYP2C19*1 allele, a low frequency of CYP2C19*2 and an absence of CYP2C19*3 allele, as it has been previously reported. [33][34][35][36][37][38] The frequency of CYP2C19*17 allele found in the present study (MM from Central Mexico) shows a minor nonsignificant difference from that found in a recent report in MM from the state of Jalisco (0.09 and 0.14, respectively). 38 The frequency of ABCB1 3435C4T in the MM population studied here is similar to that found in previous reports.…”
Section: Discussioncontrasting
confidence: 91%
“…The frequency of this allele was similar (~14%) between Mestizos from different states of Mexico and showed high variability among different indigenous groups. The Tepehuanos showed the lowest CYP2D6*4 frequency (0.385%), similar to that reported in Asians [24], and the frequency in Coras was similar to that reported in Tojolabales from Chiapas, Mexico [15].…”
Section: Resultssupporting
confidence: 85%
“…The Guarijío group had a similar CYP2D6*4 allele frequency (3.3%) to the ones reported for Tzotziles of Chiapas, Mexico (2.7%) and Purépechas of Michoacán, Mexico (2.9%) [15] and a lower frequency than reported for Mapuches from Chile (3.6%) [25] and Tzeltales from Chiapas (5.3%) [15].…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations